Alkylative Ring-Opening of Bicyclic Aziridinium Ion and Its Application for Alkaloid Synthesis - Yadav, Nagendra Nath; Lee, Young-Gun; Srivastava, Nikhil; Ha, Hyun-Joon (Frontiers in Chemistry, 2019)
Alkylative ring-opening of bicyclic aziridinium ion generated from 4-hydroxybutylaziridine with organocopper reagent was achieved successfully to afford 2-alkylsubstituted piperidine in high or moderate yield. This method allowed carbon-carbon bond formation of “non-activated” aziridine via aziridinium ion ring-opening in regio- and stereoselective manner for the first time. This newly developed reaction was applied for an efficient synthesis of alkaloid with the representative example of conine and epiquinamide.